Prácticas comerciales con los consumidores en el Derecho Español: Claves de la Ley 29/2009, de 30 de diciembre - Álvarez Lata, Natalia (Revista de Derecho, 2019)
The Spanish Act 29/2009 has adapted the Directive 2005/29/EC of the European Parliament and of the Council of 11 May 2005, concerning unfair business-to-consumer commercial practices in the internal market. The purpose of the Act, and the Directive, is to contribute to the proper functioning of the internal market and achieve a high level of consumer protection. Thereby, those documents also indirectly protect legitimate businesses from their competitors who do not play by the rules in the Directive and in the Spanish Act and thus guarantees fair competition in fields coordinated by them. In this report, we analyze the main aspects of the legal reform, directly related to influencing consumers’ transactional decisions in relation to products.